IMPACT OF OBESITY ON ENDOTOXIN-INDUCED DISSEMINATED INTRAVASCULAR COAGULATION. Issue 4 (October 2015) - Duburcq, Thibault; Tournoys, Antoine; Gnemmi, Viviane; Hubert, Thomas; Gmyr, Valery; Pattou, François; Jourdain, Mercé
<x xml:space="preserve">Abstract</x> ABSTRACT An early activation of coagulation and fibrinolysis occurs during sepsis, leading to the syndrome of disseminated intravascular coagulation (DIC). Obesity has been demonstrated to be a hypercoagulable and hypofibrinolytic state, but its impact on DIC has never been studied. In this study, we aimed to determine if obesity impairs DIC in an acute endotoxic shock model using minipigs. This was a prospective, comparative, and experimental ancillary study approved by the Animal Ethics Committee. Pigs were chosen as a clinically relevant species, resembling humans in coagulation reactions. Four groups of five "Yucatan" minipigs were studied: lean and obese control groups, a lean lipopolysaccharide (LPS) group receiving Escherichia coli endotoxin (LPS), and an obese LPS group receiving the same endotoxin dose. We measured standard coagulation parameters (prothrombin time [PT], platelet count, and fibrinogen levels), thrombin-antithrombin complexes, tissue-type plasminogen activator, and plasminogen activator inhibitor-1. All measurements were performed at baseline and 30, 60, 90, 150, and 300 min. Results were given as median with interquartile ranges. At baseline, platelet count (477 [428 – 532] G/L vs. 381 [307 – 442] G/L; P = 0.005) and fibrinogen levels (4.6 [3.8 – 5.2] g/L vs. 2 [1.8 – 2.9] g/L; P < 0.001) were significantly higher, whereas PT (80% [76% – 92%] vs. 96% [89% – 100%]; P = 0.01) was significantly lower in obese pigs compared with lean pigs. In the LPS groups, administration of endotoxin resulted in a typical hypokinetic shock with DIC. The decrease in coagulation parameters (PT, platelet count, and fibrinogen levels) and the increase in thrombin-antithrombin complexes (581 [382 – 1, 057] μg/mL vs. 247 [125 – 369] μg/mL at 150 min; P = 0.03) were significantly more important in the obese LPS group compared with those in the lean LPS group. Concerning the fibrinolytic reaction, we found a slightly more elevated increase of plasminogen activator inhibitor-1 in the obese LPS group at 300 min (481 [365 – 617] ng/mL vs. 355 [209 – 660] ng/mL; P = 0.66). In our model of endotoxic shock, obese pigs developed a more severe DIC with a more severe procoagulant response.